(3CacGQ gjLd Yf GdbGfhf hGdOhdI hGfYcGSGJgG Ydi GdacQ GdCjOdhLj (B/s - (3GdHMjQj, ajUd eMeOs ((3GdLjRI, LeghQjI eUQ GdYQHjI (B:s (3eQcR GdOQGSGJ GdYQHjI ddfTQ hGdJhRjY,s, 2017)
(3jJfGhd GdcJGH CacGQ gjLd Yf GdbGfhf hGdOhdI hGfYcGSGJgG Ydj GdacQ GdCjOdhLj Ef fXQjI GdOhdI hfXQjI GdbGfhf, hadSaI GdJGQjN dG JTcd ai adSaI gjLd EdG CLRGA efcd efXe, hHNdGa ehfJScjh GdPi dG jYGdL EdG eDSSGJ eMOOI hhGbYjI jDcO gjLd YOI eQGJ HefGSHI fXQjJg Mhd GdOhdI Cf GdfXQ Edi Ohd NUhUjI hEdi eDSSGJ NUhUjI bdjd GdCgejI(B. (3EP jLH ChdG GdfXQ Edi (B((3eGgjI GdOhdI(B) (3hdG jecf GdMce Ydi GdOhd bHd Cf fYQa eGgjI GdOhdI Ci eG gi (B((3acQI GdOhdI(B)s
(3GdaUd GdChd (B: (3MjGI gjLd heDdaGJg hGdedGeM GdQFjSjI dadaSJg(B-(3GdeHMK GdChd (B: (3MjGI gjLd heDdaGJg heUGOQ adSaJg(B-(3GdeHMK GdKGfj (B: (3GdCMOGK GdSjGSjI GdJj YGUQgG gjLd(B-(3GdeHMK GdKGdK (B: (3GdedGeM GdQFjSjI dadSaI gjLd(B-(3GdaUd GdKGfj (B: (3CacGQ gjLd Yf GdbGfhf hGdOhdI(B-(3GdeHMK GdChd (B: (3GdbGfhf hZGjGJg YfO gjLd(B-(3GdaUd GdKGdK (B: (3GfYcGSGJ adSaI gjLd(B-(3GdeHMK GdChd (B: (3GfYcGSGJ adaSI gjLd Ydi adSaI GdbGfhf(B.s
(3HHdjhLQGajI (B: (3UaMI (B101-106.s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B.s
Keywords: (3gjLd, LhQL ajdgde aQjOQjc,s -- 1770-1831; (3GdbGfhfs -- (3adSaIs; (3GdadSaI GdCdeGfjIs; (3GdefgL GdLOdjs; (3GdCjOhdhLjG GdbGfhfjIs